Physiological Concept Of Chakshuindriya W.S.R Visual Pathway - Shukla, Shubham; Sharma, Rajesh Kumar; Sharma, Dinesh Chandra (International Research Journal of Ayurveda & Yoga, 2021)
Ayurveda is an ancient health system of world which has been in practice since thousands of years. Its main aim is not only cure disease but also alleviate the humanity from all physical, mental, intellectual, or spiritual sorrow . According to Ayurveda soul which is born in a physical body in this world,Assume the world through the Indriya. Indriyas are the sadhana of Aatma.These are the tools of Aatma to gain or perceive knowledge. The Ayurveda recognizes 11(ekadash) Indriyas, chakshurindriya is one of the most important Indriya as has been said “Chakshupradhanmsarveshamindriyanam vidurvurdhah” and Acharya Charak also firstly start with Chakshuindriya in Sutra sthana . The word Chakshu means which illuminates or radiates the object and enlightens the mind about its details.These chakshurindriya are seated in two eye balls.Eyes are the windows to the mind. Chakshuindriya play a key function in our each day lives and are likely the maximum precious present we have. This global is seen to us due to the fact we’re blessed with Chakshuindriya.